Hotel Recovery Post Pandemic: Is Rebranding Required? - ERNAWATI, Ni Made; VODĂ, Mihai; JENDRA, I Wayan; TANTRI, Gusti Ayu Diah; AVRAM, Eleonora Laura (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.v13.8(64).19, 2022)
For hotel business to survive during COVID-19 Pandemic requires to conduct major adjustment in almost all aspects of operation. This qualitative study was conducted to assess the operation adjustment that may affect the hotel brand. Data was gathered from respondents comprising managers and decision-makers of 5-to-3-star hotels in Bali, Indonesia that remain open during the pandemic, using online survey and interview. The results show that during the pandemic, hotels have made major operation adjustment to survive; whilst, maintaining the same quality standard, applying meticulous CHSE ( Cleanliness Health Safety Environment) protocol, and keeping the customers informed through online promotion platforms regarding the hotel’s condition being ready to host guests. The adjustment made includes reducing operation cost, shifting target market into domestic market to maintain cash flow to cover operation, adjusting the rate and prices to adapt the weaker customer’s buying power, applying flexible booking and refund conditions, human resource policy and planning rearrangement, reducing the quantity of room offered and menu list items in Food and Beverage outlets. The hotel business resilient was owned to the professionalism of hoteliers, thus hotel rebranding is not required as the quality of the products offered is the same with those before the pandemic; at post-pandemic, it would be simply sifting the target market back to pre-pandemic.